The EM4 Addition Affect Water Absorption Time and Compost Quality in Biopore Infiltration Hole - Putri, Marsha Savira Agatha; Sulistiono, Eko; Prasidya , Denaya Andrya; Ni'am, Achmad Chusnun; Affandy, Nur Azizah (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
A biopore infiltration hole can handle organic household waste for the composting process. It can be optimized by adding an Effective Microorganism 4 (EM4) activator. This study aims to determine the effect of EM4 addition on water adsorption time, compost weight, and compost quality, according to SNI 19-7030-2004. Lamongan Islamic University's Laboratory of Environmental and Health Science determined the compost test's nutrient content. A cylindrical hole was drilled into the ground using a BIH drill with a diameter of 10 cm and a depth of 50, 75, and 100 cm, with a distance of 100 cm for each hole. The materials used in this study included domestic organic waste, leaves explicitly, and kitchen waste, a 50-ml liquid EM4